2016
DOI: 10.1007/s12565-016-0351-0
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic and retinoprotective functions of PACAP

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a 27- or 38-amino acid neuropeptide, which belongs to the vasoactive intestinal polypeptide/glucagon/secretin family. PACAP and its three receptor subtypes are expressed in neural tissues of the eye, including the retina, cornea and lacrimal gland, and PACAP is known to exert pleiotropic effects throughout the central nervous system. This review provides an overview of current knowledge regarding the cell protective effects, mechanisms of action and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 90 publications
0
29
0
Order By: Relevance
“…In the present study we demonstrated the efficacy of TAT-bound PACAP and VIP peptides to reach the retina and exert a retinoprotective effect in a model of ischemic retinopathy in rats. The retinoprotective effects of PACAP are well-documented in models of many different retinopathies (Atlasz et al 2011 , 2016 ; Shioda et al 2016 ). Intravitreal injections of PACAP have been shown to lead to robust retinoprotective effects in various models of retinal injuries (Atlasz et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we demonstrated the efficacy of TAT-bound PACAP and VIP peptides to reach the retina and exert a retinoprotective effect in a model of ischemic retinopathy in rats. The retinoprotective effects of PACAP are well-documented in models of many different retinopathies (Atlasz et al 2011 , 2016 ; Shioda et al 2016 ). Intravitreal injections of PACAP have been shown to lead to robust retinoprotective effects in various models of retinal injuries (Atlasz et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The retinoprotective effects of PACAP are well-documented and have been proven in different injury models, such as excitotoxic, ischemic, UV light-induced, traumatic, diabetic and oxygen-induced injuries (Atlasz et al 2008 , 2011 , 2016 ; Kvarik et al 2016 ; Shioda et al 2016 ; Szabadfi et al 2016 ; Vaczy et al 2016 ). VIP, on the other hand, seems to be a less potent retinoprotective peptide.…”
Section: Introductionmentioning
confidence: 99%
“…PACAP is a pleiotropic molecule, involved in a wide range of physiological processes, including cell survival during neurodegenerative conditions, stress response and cell division (Canonico et al, ; Castorina et al, ; Castorina, Giunta, Mazzone, Cardile, & D'Agata, ; Castorina, Scuderi, D'Amico, Drago, & D'Agata, ; Cavallaro et al, , ; D'Agata & Cavallaro, ; D'Agata, Cavallaro, Stivala, Travali, & Canonico, ; D'Amico et al, , ; Giunta et al, ; Maino et al, ; Maugeri, D'Amico, & Gagliano, ; Maugeri, D'Amico, & Saccone, ; Scuderi et al, ). Moreover, it is known to act as a neurotransmitter and/or a neuromodulator in the peripheral and central nervous system (Jóźwiak‐Bębenista, Kowalczyk, & Nowak, ; Shioda et al, , ; Yang et al, ). Despite recent findings have revealed that PACAP is able to rescue rat motor neurons against glutamate‐induced excitotoxicity in vitro (Tomimatsu & Arakawa, ), and confers neuroprotection to central visceromotor neurons via autocrine pathways in SOD1(G93A) mice model (Ringer et al, ), the effect of PACAP in ALS still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PACAP influences the development of the retina [15], and protects against several in vitro and in vivo retinal injuries [16,17,18,19]. In vitro, the peptide has been shown to protect whole retinal tissue cultures [20] and cell cultures from various cell types, including pigment epithelial cells [21,22] and retinal ganglion cells [23].…”
Section: Introductionmentioning
confidence: 99%